Equal Voices of Theatre: Investigating Cognition, Emotion and Behavior of Visually Impaired Audiences through Playwright and Sound Design - Puatrakul, Manussawee; Punnahitanond, Ratanasuda; Kesaprakorn, Pacharaporn; Vanichtrakul, Arthri (Executive Journal, 2025)
The study explores the creation of a stage play paradigm tailored for visually impaired audiences, addressing a significant gap in knowledge and practice. It is not only grounded in theatre, drama, music, and audience theories, but also the acknowledgment of disability as part of the human condition and the promotion of equal rights and opportunities as outlined by the United Nations’ Sustainable Development Goals. With an aim to investigate how visually impaired audiences cognitively, emotionally and behaviorally respond to five storytelling elements of the stage play script (plot, character, dialogue, sound, and spectacle), the stage play, “Turn Left Turn Right: The Musical,” with script and sound especially design for visual disability was implemented with 15 Thai visually impaired individuals in Bangkok, Thailand, during October and November B.E. 2566. Adopting a qualitative approach, an observation was conducted during the stage play and in-depth interviews were conducted after the show. Data analyses reveal that five storytelling elements of the stage play script evoke all three kinds of responses – creating mental images, joy and exaltation, and strong physical reactions (e.g., clapping, laughing); however, “sound” is the most crucial element. The participants favor comedy, and narratives that are easy to follow yet contain unexpected endings. Findings not only fill academic gaps in understanding the paradigm for visually impaired stage play, but also enable creators to create impactful and inclusive content.